Streptococcus pyogenes meningitis in children: report of two cases and literature review - Arnoni,Mariana V. (2007)
Streptococcus pyogenes meningitis (SPM) occurs sporadically, even with the increase of invasive streptococcal disease observed in the past years. We reported two cases of SPM in infants to alert pediatricians for the possibility of this agent as a cause of meningitis in previously healthy children.